Mastectomies in breast cancer: Round table XXVI Uruguayan Congress of Surgery: coordinator Alberto del Campo - del Campo, Alberto; Crestanello, Francisco; Kamaid, Emil; Mate, Miguel; Rodríguez de Vecchi, Victoriano (Cirugía del Uruguay, 1976)
The members of this Roundtable thank to the authorities of the XXVI Congress Uruguayan Surgery the designation with which have been honored. Cancer mastectmies. What techniques should we deal in the short span of a table round, at a time where, from the more conservative behaviors to the most radical have the support of authorities respectable in surgery mam.ria, justified in figures. cold from lc, s final results, how little do they differ with different techniques?